2016
DOI: 10.2177/jsci.39.140
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and clinical utility of Enzyme-linked immunosorbent assay for detection of anti-aminoacyl-tRNA synthetase antibody

Abstract: Anti-aminoacyl-tRNA synthetase (ARS) antibody is one of the myositis-specific autoantibodies to make a diagnosis of polymyositis (PM) and dermatomyositis (DM). Recently a new enzyme-linked immunosorbent assay (ELISA) kit of concurrently detected anti-ARS antibodies (anti-Jo-1, anti-PL-7, anti-PL-12, anti-EJ and anti-KS) have become to measure in the clinical setting. To evaluate the reliability of this ELISA kit, we measured anti-ARS antibodies in 75 PM and DM patients using by this ELISA assay and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Anti-Jo-1 is the only autoantibody routinely tested as widely available in most commercial ENA screening assays. An ELISA screening test has been recently developed to identify ARS, with high sensibility and specificity if compared to IP [ 26 ] and some commercially available IBs can identify some non-Jo-1 anti-synthetase antibodies [ 20 , 25 ].…”
Section: Myositis-specific Autoantibodiesmentioning
confidence: 99%
“…Anti-Jo-1 is the only autoantibody routinely tested as widely available in most commercial ENA screening assays. An ELISA screening test has been recently developed to identify ARS, with high sensibility and specificity if compared to IP [ 26 ] and some commercially available IBs can identify some non-Jo-1 anti-synthetase antibodies [ 20 , 25 ].…”
Section: Myositis-specific Autoantibodiesmentioning
confidence: 99%
“…High-resolution computed tomography (HRCT) of ILD with anti-MDA5 tends to show intralobular reticular opacities and the predominance of consolidation or ground-glass attenuation (GGA) in the lower lung fields, as well as random GGA patterns (85). In Japan, an ELISA for anti-MDA5 has been established since 2016 and is recognized as a useful assay for detecting anti-MDA5 for the earlier initiation of intensive immunosuppression therapies (60,86). We recently found that some anti-MDA5 antibody-positive patients had a novel antibody to splicing factor proline/glutamine-rich protein (SFPQ), which is known to play a role in innate immune responses (87).…”
Section: Polymyositis and Dermatomyositismentioning
confidence: 99%